Analisis Faktor Resiko Kejadian Abortus di RSUP Dr. M.Djamil Padang: Analysis of Risk Factors for Abortion at Dr. M. Djamil Padang Hospital - Lili Fajria (Fakultas Keperawatan Universitas Andalas, 2013)
One of the factors leading to high maternal mortality rate and infant mortality rate in Indonesia is the incidence of abortion . This study examines the risk factors what causes abortion incidence in pregnant women at Dr M.Djamil Padang Hospital . Research methods to approach cross-sectional descriptive analytic study . Total population of 125 people and is set as a sample in accordance with the criteria of only 52 respondents with a univariate analysis of the frequency distribution techniques and bivariate analysis with the Chi - Square formula . The results showed the incidence of abortion in Dr . M.Djamil Padang Hospital occurs more frequently in women who had one abortion, namely : 84.6 % ( 44 persons ) , while women with the incidence of abortion more than once only 15.4 % ( 8 people ) . And for occupational factors and factors associated with hemoglobin levels if the incidence of abortion showed a significant result that the work factor and the factor p = 0.000 hb levels p = 0.001. As for age, parity factor , Medical history factor and distance factors with previous pregnancies showed no significant results . Need an effort to further examine other factors that may contribute to the incidence of abortion in the mother.